Endgame in NATO's enlargement : the Baltic States and Ukraine - Bilinsky, Yaroslav (Praeger, 1999)
After briefly dealing with arguments for and against Nato's enlargement as far as Poland, the Czech Republic and Hungary, this text shows why the enlargement process must be carried forward to include the three Baltic States and Ukraine.